2011
DOI: 10.1111/j.1365-2893.2010.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the importance of mutations in the NS5A-PKR-binding domain of hepatitis C-1b virus in the era of optimally individualized therapy

Abstract: Past studies have reported that mutations in the protein kinase R-binding domain (PKRBD) sequences of hepatitis C virus (HCV) NS5A proteins are correlated with response to fixed-duration interferon (IFN)-based therapy in patients infected with HCV-1b. In this study, we investigated whether the substitutions in PKRBD, including the IFN sensitivity-determining region (ISDR) and 26 additional downstream amino acids from ISDR, will have effects upon patients infected with chronic HCV-1b in the era of individualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…According to Enomoto’s studies [8,9], a high number of aa mutations in the ISDR of HCV‐1b correlated with the response to IFN monotherapy. Most recently, additional studies conducted in Japan [23] and Taiwan [24] have provided more data to support this notion. However, contradictory data have been reported from European and United States investigators [25–27].…”
Section: Discussionmentioning
confidence: 98%
“…According to Enomoto’s studies [8,9], a high number of aa mutations in the ISDR of HCV‐1b correlated with the response to IFN monotherapy. Most recently, additional studies conducted in Japan [23] and Taiwan [24] have provided more data to support this notion. However, contradictory data have been reported from European and United States investigators [25–27].…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have demonstrated the link between different forms of non‐adherence (missing doses, early discontinuation of a regimen, interruptions during a regimen etc.) and lower SVR rates in both Western and Asian CHC patients treated with IFN+RBV‐containing regimens …”
Section: Patients’ Experience With Hcv Infectionmentioning
confidence: 99%
“…With older interferon based treatment regimens, adherence to treatment was strongly linked to treatment success in HCV infected persons. The 80/80/80 rule, indicating >80% of the cumulative dose of pegylated interferon (PEG) alfa and >80% of the cumulative dose of ribavirin (RBV) taken for >80% of the duration of a prescribed course, was associated with higher SVR in those treated with older PEG plus RBV regimens as well as those treated with these plus either boceprevir or telaprevir . Non‐completion of a full course of prescribed treatment, whether because of non‐adherence, treatment futility or other reasons, is also associated with significantly lower SVR in HCV infected persons .…”
mentioning
confidence: 99%